2015
DOI: 10.1075/is.16.3.01bra
|View full text |Cite
|
Sign up to set email alerts
|

I do not understand but I care

Abstract: Prosocial behaviour benefits another individual and occurs voluntarily. It may have a cognitive and a motivational component. The actor who benefits a recipient – for example by solving her/his problem (1) must recognize the recipient’s goal and understand how to fulfil it and (2) has to be motivated to support the recipient. In the current paper I will review recent studies on prosocial behavior in dogs and I will compare them to studies with primates. I will address the cognitive and motivational skills requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Although the co-evolution hypothesis predicts a general increase in human ability to read dog emotions and predict their behaviour (see e.g. 21 – 23 , 25 ), it is noteworthy that humans, through evolution, mainly selected dogs which were more cooperative and less aggressive 23 , 77 , 78 . Perhaps, humans evolved an increased ability to read dog positive, cooperative behaviour, rather than dog behaviour in general.…”
Section: Discussionmentioning
confidence: 99%
“…Although the co-evolution hypothesis predicts a general increase in human ability to read dog emotions and predict their behaviour (see e.g. 21 – 23 , 25 ), it is noteworthy that humans, through evolution, mainly selected dogs which were more cooperative and less aggressive 23 , 77 , 78 . Perhaps, humans evolved an increased ability to read dog positive, cooperative behaviour, rather than dog behaviour in general.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the assumption that an equal number of task-capable dogs were assigned to the experimental and control conditions may not have been valid. Study designs that do not sufficiently control for individual variation in understanding the contingencies of a prosocial task may lead to misidentification of prosocial behavior [9,30]. To address this possibility, we suggest that future studies should adopt within-subjects designs and should directly assess the ability of each dog to complete the task.…”
Section: Individual Variationmentioning
confidence: 99%
“…Previous studies investigating dog–human interactions have suggested pet dogs’ inclination toward preferring a human partner over conspecifics ( Kaminski and Marshall-Pescini, 2014 ; Bräuer, 2015 ; Nagasawa et al, 2015 ). However, in free-ranging dogs, intraspecific interactions are necessary for maintaining group stability, defending territories, and other social behaviors, for example, parental care ( Pal et al, 1998 ; Pal, 2003 ; Bonanni and Cafazzo, 2014 ; Paul et al, 2014a , b , 2015 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%